Literasi bank sampah dan asuransi sampah sebagai upaya peningkatan kesejahteraan masyarakat - Restuningdiah, Nurika; Nagari, Primasa Minerva; Dwi Jati, Fatma; Azzardina, Aulia (University of Islam Malang, 2021)
Indonesia is the second largest contributor to plastic waste after China. Despite the regulation, waste management in Indonesia has not met the standards of waste management that are environmentally sound. This forfeits the benefits of the waste management itself and brings negative impacts on public health and environment. This condition is aggravated by the costly access towards health facility. For this reason, socialization regarding waste management is needed. In addition, this program is equipped with an introduction towards waste bank and waste insurance as a practical solution. The existence of both options are expected to solve the problem of waste and health services for the community. The program aimed to help residents of RW 014 Kelurahan Tulusrejo, Malang City to comprehend the types of waste, separation of waste by category, impact on health, recycling and other details. The meetings were carried out twice from March to October 2020. The result of the agenda is that the residents continue to process waste using composter and are expected to form an independent waste bank management for local residents. Further, they are encouraged to learn more about waste insurance to manage the local waste in a more environment friendly manner.